Pengaruh Kultur Sekolah Terhadap Karakter Disiplin Siswa di SMA Negeri 2 Taruna Bhayangkara - Cindy Ineke Ferdianti; Sri Handono Budi Prastowo (Peneliti.net, 2021)
The character of discipline is very important in determining student success, but in general there are still undisciplined behaviors carried out by students at school. The character of student discipline can be formed from various factors, including school culture. This study aims to determine the effect of school culture on the discipline character of students at Taruna Bhayangkara Public High School 2. The research method used in this study is a qualitative method with a descriptive approach. The technique used to collect information in this research is interview and observation. The research location used as the object of research is Taruna Bhayangkara Public High School 2. The character of student discipline is formed through several identifications of school culture, namely waking up at Fajr time, congregational worship, ceremonies, habituation at the beginning and end of Teaching and Learning Activitie, and school rules. The school culture in Taruna Bhayangkara Public High School 2 has an effect on strengthening the disciplined character of students.